O tworzeniu republik parlamentarnych na Zakaukaziu po Wielkiej Wojnie. Wybranych uwag kilka - Lityński, Adam (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
In Russia, after the Tsar's abdication (15/2 March 1917) Azerbaijani, Armenian and Georgian national councils were spontaneously established in the Southern Caucasus. In December 1917 the Bolshevik government in Petrograd appointed its Extraordinary Commissioner for the Caucasus. Politicians of all three nations of the Caucasus appointed the Caucasus Commissariat (28/15 November 1917). At the end of January 1918, Seym of the Caucasus was convened by the Caucasus Commissariat. On 22 April 1918 the South Caucasus Seym proclaimed the creation of an independent South Caucasian Democratic Federal Republic. However, this one broke up within five weeks. Each of the three nations tried to build their own state structures. On 26 May 1918 the National Council of Georgia passed the Act of Independence of Georgia. Two days later (28 May 1918), independence was also declared by the National Councils of Azerbaijan and Armenia. The Red Army was constantly moving south. It first hit Azerbaijan and on 29 April 1920 the creation of the Azerbaijani Soviet Republic was proclaimed. From Azerbaijan, the Bolsheviks attacked and conquered Armenia. From Armenia, they attacked Georgia. On 21 February 1921 the Constitutional Assembly of Georgia passed the constitution unanimously. On 18 March 1921 Georgia surrendered. This was the end of an independent country in the Caucasus and the South Caucasus for seventy years.
Keywords: Russia in World War I; nations of the Caucasus; Bolsheviks